Efektivitas Penggunaan Anjing Penembak Jitu dalam Bantuan Pengamanan dan Penyidikan Kasus Kriminal di Satuan Polisi Pamong Praja Polda Bali - Ni Putu Tesya Sumita Dewi; H. Nurianto RS; H Sobandi (Al-Makki Publisher, 2025)
Crime is nothing new, its forms and types are increasingly developing along with the times. Various methods and efforts are made to find effective and appropriate ways to overcome this problem. The Indonesian National Police as law enforcers have the duty and responsibility to take action to prevent and overcome criminal acts. The police also have an important role as investigators. This is in accordance with the statement of Article 1 number 1 of the Criminal Procedure Code, Investigation is a subsystem of the investigation which aims to collect initial evidence which will later be used at the investigation stage. In an effort to collect tools and evidence that are indicated as traces of a crime, one of the means used by the Police is the use of tracking dogs or known as the K-9 Animal Unit.